2004
DOI: 10.1103/physrevlett.93.012701
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nuclear Structure on Sub-Barrier Hindrance inNi+NiFusion

Abstract: Fusion-evaporation cross sections for 64 Ni+ 64 Ni have been measured down to the 10 nb level. For fusion between two open-shell nuclei, this is the first observation of a maximum in the S-factor, which signals a strong sub-barrier hindrance. A comparison with the 58 Ni+ 58 Ni, 58 Ni+ 60 Ni, and 58 Ni+ 64 Ni systems indicates a strong dependence of the energy where the hindrance occurs on the stiffness of the interacting nuclei.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
56
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(57 citation statements)
references
References 27 publications
1
56
0
Order By: Relevance
“…It therefore offers an ideal test ground for a large diffuseness parameter suggested by the recent fusion data. This is particularly of interest in connection to the steep falloff phenomena of fusion cross sections at deep subbarrier energies observed recently in several systems [11,17,18,19]. This is so because the measurement of quasielastic scattering is experimentally much easier than that of fusion reaction, especially at deep subbarrier energies [16].…”
mentioning
confidence: 96%
“…It therefore offers an ideal test ground for a large diffuseness parameter suggested by the recent fusion data. This is particularly of interest in connection to the steep falloff phenomena of fusion cross sections at deep subbarrier energies observed recently in several systems [11,17,18,19]. This is so because the measurement of quasielastic scattering is experimentally much easier than that of fusion reaction, especially at deep subbarrier energies [16].…”
mentioning
confidence: 96%
“…It would also be interesting to extend the measurement of fusion cross sections at lower energies for these systems in order to better understand the role of transfer reactions on the deep sub-barrier fusion hindrance recently observed [84,85].…”
Section: Discussionmentioning
confidence: 99%
“…The main reason that does allow one to add an additional repulsive force to the NN interaction is the Pauli exclusion principle which does not permit the total density in the overlap region to exceed the saturated density. Recently it has been shown that this modification explains the steep-fall off effect in the interaction of the heavy ions [13][14][15][16][17][18][19][20]. As this repulsive term affects the internal and external parts of the nuclear potential in places where the fusion reaction is sensitive to them (see Fig.…”
Section: Introductionmentioning
confidence: 97%